Physicochemical and Sensory Properties of Crispy Waffles with MOCAF, Modified Banana Flour, and Sodium Bicarbonate - Maria Michelle Angela Chairina; Rosida Rosida; Andre Yusuf Trisna Putra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study evaluated the effects of MOCAF: modified banana flour ratio and sodium bicarbonate concentration on the physicochemical, textural, and sensory properties of crispy waffles as a local flour-based snack prototype intended for gluten-free product development. A factorial completely randomized design was used with two factors: MOCAF: modified banana flour ratios of 85:15, 75:25, and 65:35, and sodium bicarbonate concentrations of 0.1, 0.3, and 0.5%. Physicochemical and texture-scoring data were analyzed by ANOVA followed by Duncan’s Multiple Range Test at 5% significance, while hedonic data were analyzed using the Friedman test. The flour ratio significantly affected moisture and starch contents, sodium bicarbonate affected starch content, and the factor interaction significantly affected protein, fat, crude fiber, hardness, and fracture. Hedonic color, aroma, taste, and texture did not differ significantly, whereas texture scoring differed among treatments. The best formulation was obtained from the 65:35 MOCAF: modified banana flour ratio with 0.1% sodium bicarbonate, producing crispy waffles with 2.68% moisture, 1.78% ash, 3.97% protein, 24.03% fat, 2.93% crude fiber, 31.73% starch, 3.65% total dietary fiber, 3.06% resistant starch, 515.42 N hardness, and 492.90 N fracture. The formulation showed balanced physicochemical, textural, and sensory properties and has potential for further development as a gluten-free crispy waffle prototype based on local flours. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production